Metal-Organic Frameworks Based on Zinc(II) and Benzene-1,3,5-Tricarboxylate Modified Graphite: Fabrication and Application as an Anode Material in Lithium-Ion Batteries - Witri Wahyu Lestari; Wulan Cahya Inayah; Fitria Rahmawati; Larasati Larasati; Agus Purwanto (Institute for Research and Community Services (LPPM) ITB, 2020)
This research was aimed at synthesizing metal-organic frameworks (MOFs) based on zinc(II) and a benzene-1,3,5-tricarboxylate (BTC) linker in combination with graphite as anode material in lithium-ion batteries. The MOFs were prepared using sonochemical and solvothermal methods, which led to different materials: [Zn3(BTC)2·12H2O] (MOF 1) and [Zn(BTC)·H2O·3DMF] (MOF 2). The produced materials were characterized by powder X-ray diffraction (PXRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), thermogravimetric/differential thermal analysis (TG/DTA), and a battery analyzer. Refinement of the XRD data was performed using the Rietica and Le Bail method. Sharp and intense peaks indicated that the materials had a high degree of crystallinity. The morphology of the materials as analyzed by SEM was cubic, with an average crystal size of 8.377 ± 4.276 µm for MOF 1 and a larger size of 16.351 ± 3.683 µm for MOF 2. MOF 1 was thermally stable up to 378.7 °C while MOF 2 remained stable up to 341.8 °C, as demonstrated by thermogravimetric analysis. The employment of the synthesized materials as anode in a lithium ion battery was proved to yield higher specific capacity and cycle stability compared to those using a graphite anode. The lithium-ion battery with 5 wt% MOF 1 exhibited the highest performance with an efficiency of 97.28%, and charge and discharge specific capacities of 123.792 and 120.421 mAh/g, respectively.